Photoluminescence study of Sm3+-Yb3+ co-doped tellurite glass embedding silver nanoparticles - Reza Dousti, M. (2015)
We report on the upconversion emission of Sm3+ ions doped tellurite glass in the presence of Yb3+ ions and silver nanoparticles. The enhancement of infrared-to-visible upconversion emissions is achieved under 980 nm excitation wavelength and attributed to the high absorption cross section of Yb3+ ions and an efficient energy transfer to Sm3+ ions. Further enhancements are attributed to the plasmonic effect via metallic nanoparticles resulting in the large localized field around rare earth ions. However, under excitation at 406 nm, the addition of Yb3+ content and heat-treated silver nanoparticles quench the luminescence of Sm3+ ions likely due to quantum cutting and plasmonic diluent effects, respectively.